Optimization of cutting force and temperature during Ti6Al4V/Al7050 laminate composites elliptical vibration turning. (August 2019) - Shi, Wentian; Hou, Yanjun; Kong, Chao; Liu, Yude
In this paper, the Taguchi method has been used to optimize cutting parameters in the turning of Ti6Al4V/Al7050 laminates under elliptical vibration cutting. The turning tests were conducted based on L16 orthogonal array, which was designed by the Taguchi method. The analysis of variance was used to calculate impacts of cutting parameters on cutting forces and temperature. The analysis of results showed that the vibration frequency is the dominant factor on the cutting force and the vibration amplitude is a dominant factor affecting the temperature. The analysis of variance was also used to predict the cutting force and temperature in the turning of Ti6Al4V/Al7050 laminate. A good agreement between the predicted and the actual value can be found in the results.